Hydrothermal liquefaction of olive mill solid waste using transition metal doped montmorillonite catalyst via biorefinery approach - Ozcan, Burak; Hosgun, Emir Zafer; Hosgun, Halit Levent; Bozan, Berrin (Taylor & Francis Inc, 2025)
The olive oil industry produces significant waste that contributes to escalating environmental damage. In this study, catalytic hydrothermal liquefaction (HTL) of solid olive mill waste with clays (montmorillonite, kaolin, and bentonite) was carried out at 300 degrees C for 30 min to recover the bio-oil. The yield of the bio-oil without a catalyst was 23.92%. The highest bio-oil yield of 28.56% was obtained with montmorillonite (MMT). Subsequently, various transition metals (chromium, cobalt, zinc, manganese, and nickel) were loaded on MMT by pillaring method and characterized by XRD, XRF, BET, and SEM methods. The yield of bio-oil products increased significantly with the addition of transition metals to MMT catalysts. The Ni/MMT catalyst showed the highest bio-oil yield (38.23%). The elemental analysis shows that the oxygen content of the bio-oil was reduced by the catalysts. The maximum calorific value of the bio-oil (36.13 MJ/kg) was achieved with the MMT catalyst, which was significantly higher than that of the feedstock (19.92 MJ/kg). The energy balance results showed that Ni/MMT had the best positive effect on energy recovery and energy consumption, although the MMT catalyst had the highest HHV. Furthermore, the catalyst significantly affected the composition of hydrocarbons, acids, esters, amides, and heterocyclic compounds in the bio-oil.
Keywords: Hydrothermal liquefaction; montmorillonite; olive mill solid waste; bio-oil